2022
DOI: 10.1088/1752-7163/ac8ea1
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of Covid-19 detection using breath analysis by high-pressure photon ionization time-of-flight mass spectrometry

Abstract: Background: SARS-CoV-2 has caused a tremendous threat to global health. PCR and antigen testing have played a prominent role in the detection of SARS-CoV-2-infected individuals and disease control. An efficient, reliable detection tool is still urgently needed to halt the global COVID-19 pandemic. Recently, FDA emergency approved VOC as an alternative test for COVID-19 detection. Methods and materials: In this case-control study, we prospectively and consecutively recruited 95 confirmed COVID-19 patients and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Therefore, UVP-TOFMS and GC-MS complement each other. GC-MS is conducive to discovering new biomarkers [21], and UVP-TOFMS is suitable for rapid sample analysis [24]. In this study, the performance of exhaled breath analysis for diagnosis of UGI cancer based on GC-MS and UVP-TOFMS was comparable, with AUC of 0.959 and 0.994, respectively.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, UVP-TOFMS and GC-MS complement each other. GC-MS is conducive to discovering new biomarkers [21], and UVP-TOFMS is suitable for rapid sample analysis [24]. In this study, the performance of exhaled breath analysis for diagnosis of UGI cancer based on GC-MS and UVP-TOFMS was comparable, with AUC of 0.959 and 0.994, respectively.…”
Section: Discussionmentioning
confidence: 66%
“…UVP-TOFMS is a promising exhaled breath analysis tool with the advantages of fast analysis, high sensitivity, and no sample preconcentration [23]. By analyzing VOCs in exhaled breath, UVP-TOFMS has been used in the diagnosis of COVID-19 [24], lung cancer [25], and esophageal cancer [26]. The UVP-TOFMS consisted of a vacuum ultraviolet lamp ion source, a radiofrequency quadrupole ion guide, and an orthogonal acceleration time-of-flight mass analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…All samples were detected within 2 to 4 hours after sampling. Our previous studies have shown that the PEEK breath bags had a limited impact with relative differences <20% on VOCs in the collected breath samples in 24 hours 17 . Exhaled breath was collected after the neuropsychological assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that the PEEK breath bags had a limited impact with relative differences <20% on VOCs in the collected breath samples in 24 hours. 17 Exhaled breath was collected after the neuropsychological assessment. The neuropsychologists and data analysis team were blinded to the clinical diagnoses and the results of breath testing.…”
Section: Exhaled Breath Collectionmentioning
confidence: 99%
“…Photoionisation(PI)-based methods for breath analysis is a growing area of research 36 . Recently, Zhang et al 37 achieved good sensitivity detecting SARS-COV-2 infection using PI with high-resolution MS (HRMS) and machine learning (ML) based on breath VOC pro les. Zhou et al 38 modi ed a commercial APPI front end to facilitate breath sampling/analysis 38 ; using a high-resolution Q-ToF and collision induced dissociation (CID) they reported identi cation of new metabolites in breath.…”
Section: Introductionmentioning
confidence: 99%